The impact of untreated hearing loss on depression, anxiety, stress, and loneliness in tonal language-speaking older adults in China - Fu, Xinxing; Eikelboom, Robert H.; Liu, Bo; Wang, Shuo; Jayakody, Dona M. P. (Frontiers in Psychology, 2022)
Background: Age-related hearing loss, mental health conditions and loneliness commonly affect older adults. This study aimed to determine whether untreated hearing loss is independently associated with depression, anxiety, stress, and loneliness in tonal language-speaking older adults in China. Study design: Observational, cross-sectional study. Methods: 293 older adults (111 males, M=70.33±4.90 years; 182 females, M=69.02±4.08 years) were recruited. All participants completed a pure tone audiometric hearing assessment, and provided information on living arrangements, marital status, leisure activities, tobacco and alcohol use, and medical history. The Mandarin version of the De Jong Gierveld Loneliness Scale was used to measure loneliness and the Mandarin version of the 21-item Depression Anxiety Stress Scale (DASS-21) was used to assess a range of symptoms common to depression, stress, and anxiety of the participants. The analysis focused on determining the predictors of depression, anxiety and stress, and the predictors of measures of loneliness. Results: Multiple stepwise regression analyses revealed that the emotional loneliness (β=0.303, p<0.001) and living status (β=0.110, p=0.048) significantly predicted DASS depression scores; emotional loneliness (β=0.276, p<0.001) and a history of vascular disease (β=0.148, p=0.009) were significantly related to DASS anxiety scores; emotional loneliness (β=0.341, p<0.001) and a history of vascular disease (β=0.129, p=0.019) significantly predicted DASS stress scores. Furthermore, multiple stepwise regression analyses showed that DASS stress scores (β=0.333, p<0.001), education years (β=-0.126, p=0.020), marriage status (β=0.122, p=0.024) and a history of vascular disease (β=0.111, p=0.044) significantly predicted emotional loneliness; four-frequency average hearing loss (β=0.149, p=0.010) and DASS stress scores (β=0.123, p=0.034) significantly predicted social loneliness scale; four-frequency average hearing loss (β=0.167, p=0.003) and DASS stress scores (β=0.279, p<0.001) also significantly predicted overall loneliness. There were no significant associations with high-frequency hearing loss. Conclusion: This study revealed that loneliness has a significant relationship both with hearing loss and aspects of mental health in an older adult Mandarin-speaking population. However, mental health was not significantly associated with hearing loss in this population.